The Influence of Chromosomal Polymorphism on Embryo Development and Embryonic Molecular Karyotype in Preimplantation Genetic Testing for Chromosomal Translocation - Li, Gang; Shi, Weiyi; Niu, Wenbin; Xu, Jiawei; Guo, Yihong; Su, Yingchun; Sun, Yingpu (Frontiers in Physiology, 2020)
Chromosomal polymorphisms (CPMs) are regarded as harmless chromosomal variation. But we explored the influence of CPM on embryonic development and molecular karyotype in chromosomal translocation (CT) patients. Our data showed The high-quality blastocyst rate of CTCPM was significantly lower than that for CT (26.78% vs. 38.89%), and Abnormal embryo rates of CTCPM were significantly higher than those for CT (78.64% vs. 68.93%). Paternal carriers instead of maternal contributed to the influence.